PENERAPAN PEWARNAAN GRAF MENGGUNAKAN ALGORITMA WELCH-POWELL UNTUK KEEFEKTIFAN PENGATURAN TRAFFIC LIGHT DI SIMPANG MAJESTIK - Marpaung, Faridawaty (JURNAL KELUARGA SEHAT SEJAHTERA, 2018)
ABSTRACTThe research method includes several stages, namely data retrieval from DISHUBKOMINFO, namely the red and green light duration data at the Majestik intersection, transforming the intersection with the current into a graph, coloring each node in the graph using the Welch-Powell algorithm. Based on the calculation of the level of effectiveness of the total duration of the secondary data traffic arrangement with the new data at the Majestik intersection, it can be seen that at the interval of 15.00 - 20.00 the effectiveness of the green light duration increases by 6.81% and the red light duration decreases by 26.01% vehicle concentration is low. Keywords: Traffic Light, Graph Coloring, Welch “ Powell